Kontribusi Muhammad Abdul Mannan Terhadap Skema Jaminan Sosial dalam Peradaban Ekonomi Islam Modern - Hakiki, Muhamad Fuji; Suganda, Ahmad; Janwari, Yadi (Jurnal Ilmiah Ekonomi Islam, 2024)
This research examines the theoretical and practical contributions of Muhammad Abdul Mannan (1938-2021) to the modern Islamic economic civilization. Employing primarily qualitative research methods, Mannan, a pioneering figure, significantly shaped Islamic economics into a distinct social science discipline. His unique perspective on the Islamic approach to social security systems in Islamic economics enriches theoretical knowledge in modern Islamic economics. As a visionary, lifelong educator, and philanthropist, Mannan left a lasting impact by establishing various institutions, including the Social Islamic Bank Limited (SIBL), contributing to the socio-economic development of Bangladesh. He dedicated his talent and hard work to establish SIBL, testing its three-sector model (formal, informal, and voluntary) to alleviate poverty and inequality in society. Introducing Cash Waqf through SIBL as a novel interest-free microcredit strategy for empowering impoverished families, Mannan pioneered the concept in Bangladesh, marking a significant advancement in the realm of Islamic economics.